2021
DOI: 10.47371/mycosci.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and phytotoxicity of ophiobolins produced by <i>Bipolaris setariae</i>

Abstract: The Bipolaris setariae NY1 strain, isolated from a diseased green foxtail plant in Henan Province, China, showed strong pathogenicity towards green foxtail. In order to clarify the role of phytotoxic substances in the fungal pathogenicity, bioassay-directed isolation and bioactivity assays of secondary metabolites produced by the fungal strain were carried out. Five ophiobolins were obtained: 3-anhydro-ophiobolin A, 6-epi-ophiobolin A, 6-epi-ophiobolin B, 3-anhydro-6-epi-ophiobolin B and ophiobolin I. Bioassay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Zhao et al reported that 3-anhydroophiobolin A and 6-epi-ophiobolin A showed strong phytotoxicity on green foxtails whereas 6-epi-ophiobolin B and 3-anhydro-6-epi-ophiobolin B appeared to be almost inactive. 14 These data revealed that the C-ring formed by C-14 and C-17 contributed to their phytotoxicity. Sugawara et al reported four new ophiobolins with 7-CH 2 OH, which showed the potential phytotoxicity for the rice leaves, indicating that 7-CH 2 OH might be an active group.…”
Section: T H Imentioning
confidence: 88%
See 2 more Smart Citations
“…Zhao et al reported that 3-anhydroophiobolin A and 6-epi-ophiobolin A showed strong phytotoxicity on green foxtails whereas 6-epi-ophiobolin B and 3-anhydro-6-epi-ophiobolin B appeared to be almost inactive. 14 These data revealed that the C-ring formed by C-14 and C-17 contributed to their phytotoxicity. Sugawara et al reported four new ophiobolins with 7-CH 2 OH, which showed the potential phytotoxicity for the rice leaves, indicating that 7-CH 2 OH might be an active group.…”
Section: T H Imentioning
confidence: 88%
“…Then, Fr.2 (11.0 g) was fractionated on a silica gel column using a petroleum ether−acetone (100:1−1:1) gradient to give three fractions (Fr. 13 C NMR (125 MHz, CDCl 3 ), Tables 1 and 3 13 C NMR (125 MHz, CDCl 3 ), Tables 1 and 3 13 C NMR (125 MHz, CDCl 3 ), Tables 1 and 3 13 C NMR (125 MHz, CDCl 3 ), Tables 1 and 3 Bipolaricin O (6): [α]25 D + 69.0 (c 0.1, MeOH); UV (MeOH) λ max (log ε) 210 (3.44) nm; IR (neat) ν max 2962, 1740, 1698, 1228, and 1026 cm −1 ; 1 H NMR (500 MHz, CDCl 3 ) and 13 C NMR (125 MHz, CDCl 3 ), Tables 1 and 3 13 C NMR (150 MHz, CDCl 3 ), Tables 2 and 4 (14), monoclinic, a = 16.8737(6) Å, b = 6.3485(3) Å, c = 21.0188(7) Å, U = 2077.43(14) Å 3 , T = 116.70 (14), α = 90.00°, β = 112.683(4)°, γ = 90.00°, space group I2 (no. 5), Z = 4, μ(Cu Kα) = 0.554, F(000) = 808, crystal size 0.35 × 0.08 × 0.03 mm 3 , 8792 reflections measured, 3521 unique (R int = 0.0340), which were used in all calculations.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All experiments were repeated at least three times. The effects were recorded after 3 days of observation ( Zhao et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…255 There are nearly 60 identied congeners of ophiobolins and studies predominantly focus on their bactericidal, fungicidal, nematocidal, and anti-calmodulin effects. [256][257][258][259][260][261] Fig. 6 shows representative members with key structural variations involving the C3, C14, and C21 oxidation states, C6 stereochemistry, and whether a D (tetrahydrofuran) ring is present.…”
Section: Ophiobolin Amentioning
confidence: 99%